Predictors of futile recanalization in patients undergoing endovascular treatment in the DIRECT-MT trial. (2nd September 2021) - Zhou, Tengfei; Yi, Tingyu; Li, Tianxiao; Zhu, Liangfu; Li, Yucheng; Li, Zhaoshuo; Wang, Meiyun; Li, Qiang; He, Yingkun; Yang, Pengfei; Zhang, Yongwei; Li, Zifu; et al.
Abstract : Background: Futile recanalization—when patients have a successful recanalization but fail to achieve a satisfactory functional outcome— is a common phenomenon of endovascular treatment of acute ischemic stroke (AIS). The present study aimed to identify the predictors of futile recanalization in AIS patients who received endovascular treatment. Methods: This is a post-hoc analysis of the DIRECT-MT trial. Demographics, clinical characteristics, acute stroke workflow interval times, biochemical parameters, and imaging characteristics were compared between futile and meaningful recanalization groups. Multivariate analysis was performed to identify the predictors of futile recanalization. Results: Futile recanalization was observed in 277 patients. In multivariable logistic regression analysis, older age (p<0.001), higher baseline systolic blood pressure (SBP) (p=0.032), incomplete reperfusion defined by extended Thrombolysis In Cerebral Infarction (eTICI) grades (p=0.020), and larger final infarct volume (FIV) (p<0.001) were independent predictors of futile recanalization. Conclusions: Old age, high baseline SBP, incomplete reperfusion defined by eTICI, and large FIV were independent predictors of futile recanalization after endovascular therapy for AIS.